Negotiating Tradition and Digital Technology in Family-Based Informal Learning: an Ethnographic Study of Dayak Kanayant Parenting Practices - Sudirman Sudirman; Dwi Surti Junida (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to examine how Dayak Kanayant families in West Kalimantan negotiate traditional parenting values with the influence of digital technology in the context of family-based informal learning. The study responds to the limited attention in educational technology scholarship to indigenous family environments as informal learning spaces shaped by cultural logic, kinship relations, and distinctive forms of digital mediation. Methods:  This study employed a qualitative ethnographic approach in Desa Terap, Toho District, Mempawah Regency, West Kalimantan. Data were collected over four months through in-depth interviews, participant observation, field notes, and documentation involving parents, grandparents, and children. Data analysis was conducted using a thematic-interpretative approach through repeated reading of interview transcripts and field notes, initial coding, theme development, ethnographic interpretation, and triangulation across interviews, observations, and documentation. Findings: The findings show that parenting in Dayak Kanayant families is practiced collectively through the involvement of parents, grandparents, and extended family members. Children learn discipline, respect for elders, cooperation, and cultural responsibility through observation, imitation, and direct participation in family and community activities. The presence of digital technology, particularly smartphones, creates new tensions by shifting some children’s attention from communal activities to screen-based activities. However, digital technology is neither fully rejected nor simply accepted. Families negotiate its use by regulating screen time, prioritizing customary and family obligations, and using digital communication to maintain emotional and educational connections with parents working outside the village. Research Implications: The findings suggest that educational technology should not only be understood as a school-based learning tool, but also as a culturally mediated learning resource within family environments. Therefore, digital literacy and family education programs need to consider kinship structures, intergenerational authority, and the local values of indigenous communities. Originality: This study contributes to educational technology scholarship by showing how indigenous families negotiate digital technology through culturally embedded parenting practices, rather than experiencing technology merely as a disruptive force against tradition.